SISTEM PENDUKUNG KEPUTUSAN PENENTUAN PEMAIN TERBAIK MENGGUNAKAN METODE PROFILE MATCHING Studi Kasus: SSB Putra Marinir (PUMA) - Muammar Khaddafi; Suryaningrat (CV. Multi Kreasi Media, 2022)
In determining the best player at SSB Putra Mandiri (PUMA) Jakarta, there are several criteria factors in making decisions so that they get the right decision. The criteria are skill, personality and responsibility. At this time, the process of evaluating the performance of players at SSB Putra Mandiri (PUMA) does not yet exist, so it cannot determine the decision of the best player in Putra Mandiri (PUMA) Jakarta. For this reason, the decision support system (DSS) is very helpful in terms of making decisions, which are then analyzed using the profile matching method. By using the profile matching method, SSB Putra Mandiri (PUMA) Jakarta can make decisions in assessing the performance of players according to their abilities. This study was to determine the ranking/weighted value in the assessment of the best players at SSB Putra Mandiri (PUMA) Jakarta